University Student and Faculty Needs, Barriers, and Expectations of International Efforts and Opportunities: A Closer Look at One Land-Grant University’s College of Agriculture - Stuart Estes; Maggie Jo Hansen; Leslie D Edgar (Journal of International Agricultural and Extension Education, 2016)
International academic opportunities have gained increased attention among students, faculty, and administration at American universities. It is important for agriculturalstudents to have an awareness and understanding of agricultural policy and issues in the United Statesand other countries. Also,faculty who have personal and professional ties internationally are often the link for these students to engage in globalexperiences. This study used descriptive survey methodology to assess students (N=773) and faculty (N=85) at the University of Arkansasabouttheir perceptions of international experiences, as well as what they saw as the most influential barriers and influencers to participating in international experiences. Students notedtheir parents (M= 3.30) as the most impactful influencefor deciding whether or not to engage in an international experience, and cost (M= 3.92) was perceived as the most influential barrier to an international experience. Faculty noted money (84.2%) and time (80.7%) as barriers, and about one-half of the faculty wishedto collaborate with institutions in Europe. Faculty perceived thatinstitutional financial support should be provided to both faculty and students (74.1%). Thisstudy notes student influencers and barriers and faculty needsand providesrecommendations for improving international learning experiences and opportunities for future research.
Keywords: agricultural education; international experiences; international experienceinfluencers and barriers; study abroad